Strukturalno-stylistyczne cechy gatunku a kształtowanie relacji nadawczo-odbiorczych w telenoweli paradokumentalnej "Szkoła" - Szkudlarek-Śmiechowicz, Ewa (Acta Universitatis Lodziensis. Folia Litteraria Polonica, 2017)
The article is aimed at analysing the genre, structural, stylistic, pragmatic and cognitive traits of the documentary soap titled “Szkoła” (“The School”) which is an example of the process of widening the sphere of tabloid media communication. The inclusion of para-documentaries in institutional, educational and care-providing discourse is another step towards strengthening and consolidating tabloid culture and communication. It seems that the institutional bodies involved in this discourse are under its influence so strongly that they do not see its tabloid character, and what follows – its negative results.